IMF Staff papers : Volume 4 No. 2. (IMF Staff Papers; IMF Staff Papers, 1955)
This paper reviews the impact of liberalization of intra-European trade in the framework of the Organization for European Economic Cooperation (OEEC). Commercial relations have been most intensive between the industrialized countries of Western Europe, which have carried on a considerable trade with each other both in manufactured products and in such industrial raw materials as they produce in substantial quantities. With the depression of the thirties, international trade declined sharply, and normal trade relations between European countries were disrupted by the widespread tendency to protect domestic markets. OEEC initiatives for the progressive achievement of a single market were taken in various fields. Early experience, however, showed that it would be premature to attempt to promote economic integration through close and effective international planning; and since that time, coordinated action relating to internal financial stability, investments, manpower, has been tentative and fragmentary.